2012
DOI: 10.1111/j.1440-1746.2011.07041.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of T1 colorectal carcinoma with special reference to criteria for curative endoscopic resection

Abstract: Even in cases of colorectal carcinoma with deep submucosal invasion, the risk of lymph node metastasis is minimal under certain conditions. Thus, even for such cases, endoscopic incisional biopsy can be suitable if complete en bloc resection is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
132
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(139 citation statements)
references
References 35 publications
(63 reference statements)
5
132
2
Order By: Relevance
“…16 In patients receiving additional major surgery according to the recommendation, however, metastasis was found in 15 to 16%, and up to 80% or more might undergo unnecessary surgery in terms of lymph node metastasis. 15,23 According to the recommendation of the Japanese Society for Cancer of the Colon and Rectum guidelines 2010, additional major surgery would not be recommended for 121 (15%) of the 806 patients in the present study and lymph node metastasis could be found in only 1 (1%), whereas additional surgery would be recommended for 685 patients (85%) and lymph node metastasis could be found in 96 (14%). This concept may be beneficial but still many patients would have unnecessary surgery.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…16 In patients receiving additional major surgery according to the recommendation, however, metastasis was found in 15 to 16%, and up to 80% or more might undergo unnecessary surgery in terms of lymph node metastasis. 15,23 According to the recommendation of the Japanese Society for Cancer of the Colon and Rectum guidelines 2010, additional major surgery would not be recommended for 121 (15%) of the 806 patients in the present study and lymph node metastasis could be found in only 1 (1%), whereas additional surgery would be recommended for 685 patients (85%) and lymph node metastasis could be found in 96 (14%). This concept may be beneficial but still many patients would have unnecessary surgery.…”
Section: Discussionmentioning
confidence: 73%
“…Although the implication of budding/sprouting in deeply invasive colorectal cancer was first reported in 1989, 25 many studies have also focused on budding/sprouting as a risk factor of lymph node metastasis in T1 colorectal cancer. [12][13][14][15][26][27][28][29][30][31][32] Some investigators refer to findings similar to budding/sprouting as 'unfavorable histology at the invasive front,' 33 'focal dedifferentiation,' 34 or 'tumor cell dissociation,' 35 although the definition is not always consistent. 13,25,32,36 In the evaluation of budding/sprouting, we adopted the definition of Ueno et al 13 because it is widely used and has good reproducibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported an incidence of LN metastasis of only 1.2% (95% CI 0.25-3.48%) in T1 CRC without three of the four risk factors (i.e. all but submucosal invasion depth <1,000 μm) for LN metastasis described in the JSCCR guideline [16]. Furthermore, in another study, we suggested the condition of the muscularis mucosae to be an indicator for LN metastasis in T1 CRC [17].…”
Section: Discussionmentioning
confidence: 99%
“…The investigators concluded that even in cases of CRC with deep submucosal invasion, the risk of lymph node metastasis is minimal under certain conditions. Thus, even for such cases, endoscopic incisional biopsy could be suitable if complete en bloc resection was achieved (3).…”
mentioning
confidence: 99%